2021
DOI: 10.51244/ijrsi.2021.8407
|View full text |Cite
|
Sign up to set email alerts
|

Role of botanical essential oils as a therapy for controlling coronavirus (SARS-CoV-2) disease (Covid-19)

Abstract: This review paper presented on the basis of extensive literature survey updated the importance of plant essential oils in controlling many diseases, particularly coronavirus (SARS-CoV-2) disease outbreak. Plant essential oils are valuable natural products, and used as a raw materials in aromatherapy, phytotherapy, perfumery, cosmetics, spices and nutrition. Aromatic plants produced a diversity of chemical constituents with the potential to inhibit viral replication. Essential oils have several biological prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(143 citation statements)
references
References 31 publications
2
141
0
Order By: Relevance
“…[27][28][29][30] During the COVID-19 pandemic, the consumption of carnation as an additive to food or drink to relieve throat pain has increased. 31 A randomized clinical trial of a blend that contains carnation buds demonstrated a boost in energy levels among post-COVID-19 female patients. 32 In addition, carnation has antibacterial, antiviral, and antifungal effects, and is used to kill germs in dental creams, toothpaste, mouthwash formulations, and throat sprays.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] During the COVID-19 pandemic, the consumption of carnation as an additive to food or drink to relieve throat pain has increased. 31 A randomized clinical trial of a blend that contains carnation buds demonstrated a boost in energy levels among post-COVID-19 female patients. 32 In addition, carnation has antibacterial, antiviral, and antifungal effects, and is used to kill germs in dental creams, toothpaste, mouthwash formulations, and throat sprays.…”
Section: Discussionmentioning
confidence: 99%
“…TVO has antiseptic, antimicrobial, astringent, anthelmintic, healing, tonic, carminative, antiseptic, antiviral, and anti-inflammatory effects [ 107 , 114 ]. It exhibits intense antibacterial activity against many pathogenic bacteria and can be used as an alternative antibacterial and antioxidant agent [ 110 ].…”
Section: Essential Oils With Potential Anti-acne Effectsmentioning
confidence: 99%
“…Thymol does not reduce the formation of oedema but causes irritation, possibly mediated by the release of histamine and prostanoids. Thymol is active against enterobacteria and cocci bacteria [ 114 ]; however, crude essential oil is the most effective. Ahmad et al [ 113 ] investigated the antimicrobial interactions between TVO components, determining the contribution of less active ingredients to enhancing the oil’s antimicrobial activity.…”
Section: Essential Oils With Potential Anti-acne Effectsmentioning
confidence: 99%
“…Terminalia arjuna is commonly used to damage gastric, stomach ulcers, diarrhea, and dysentery and provides a healthy life, Lawsonia inermis is used to prefer healthy gum, and healthy hair and reduces arthritis pain and one of the important medicine to reduce headaches if they occurred by the heat of the sun. Azadirachta indica is used to stay with healthy life from treated acne, nourishing the skin, treating wounds, use to reduce dandruff, joint pain types of disease and Ocimum tenuiflorum is used to treat kidney stones, alleviate fever and headaches, provide a healthy heart, healthy eye, healthy oral and fights against acne and also known as the big source of vitamin K [3]. There are different types of deep learning algorithms to predict the disease of Phytomedicine tree leaves but in these approaches, there have been used the Keras pre-trained model as VGG19, ResNet152V2, Xception, InceptionResNetV2 and for object detection algorithms, YOLOv5 have been used to detects the Phytomedicine tree's leaves disease affection status as it is affected by disease or not.…”
Section: Introductionmentioning
confidence: 99%